2008
DOI: 10.1002/adsc.200700564
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chiral Biheteroaromatic Diphosphine Oxides for Lewis Base Activation of Lewis Acids in Enantioselective Allylation and Epoxide Opening

Abstract: Enantiomerically pure biheteroaromatic diphosphine oxides were synthesised and tested as organocatalysts in two different reactions involving trichlorosilyl compounds. The allylation of aldehydes with allyl(trichloro)silane afforded homoallylic alcohols in fair to good yields and up to 95% ee. Preliminary experiments showed that this new class of metal-free catalysts was able also to promote the stilbene oxide opening by addition of tetrachlorosilane with enantioselectivity higher than 80%. The interesting res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Noteworthy, a more electron poor chiral phosphine oxide, such as BITIANPO 3 , promoted the reaction in very low yield (9%), although with good diastereo‐ and enantioselectivity (96/4 syn/anti , 79% ee ). These results confirm a trend already observed in the chiral Lewis base‐promoted enantioselective addition of allyltrichlorosilane to aldehydes20 and pointed to the importance of the electronic properties of the chiral phosphine oxide in fine‐tuning the catalyst’s performance.…”
Section: Methodssupporting
confidence: 88%
“…Noteworthy, a more electron poor chiral phosphine oxide, such as BITIANPO 3 , promoted the reaction in very low yield (9%), although with good diastereo‐ and enantioselectivity (96/4 syn/anti , 79% ee ). These results confirm a trend already observed in the chiral Lewis base‐promoted enantioselective addition of allyltrichlorosilane to aldehydes20 and pointed to the importance of the electronic properties of the chiral phosphine oxide in fine‐tuning the catalyst’s performance.…”
Section: Methodssupporting
confidence: 88%
“…This indicated that the substituents on the phenyl ring had a remarkable effect on the enantioselectivities in the desymmetrization of meso -epoxides [84]. Benaglia [85] and colleagues have developed chiral phosphine oxides OC-64 and OC-69 for the enantioselective desymmetrization of meso -stilbene oxide to provide the corresponding vicinal chlorohydrin 96 in up to 82% ee.…”
Section: Reviewmentioning
confidence: 99%
“…We were interested in applying our catalytic methodologies to the transformation; in our previous studies of Lewis‐based catalyzed reactions in the presence of silicon tetrachloride the use of biheteroaromatic diphosphine oxides, more electron‐rich than the commonly used binaphthyl diphosphine derivatives, has often led to the formation of the desired products with enantioselectivities higher than those obtained with BINAPO; therefore we decided to investigate the behavior of ( S )‐tetramethyl‐bithiophene phosphine oxide, ( S )‐TetraMe‐BITIOPO, in the direct double aldol reaction between aryl methyl ketones and aromatic aldehydes.…”
Section: Introductionmentioning
confidence: 99%